Does intellectual capital have an impact on company risk and performance?: Effect of moderation political connection - Mahardhika, Budi Wahyu; Anshori, Muslich; Setiawan, Rahmat (Edelweiss Applied Science and Technology, 2024)
This study looks at the effect of intellectual capital on firm performance and risk as well as the moderating effect of political connections. Companies in the current economic era are required to pay more attention to intangible resources. Intellectual capital is considered as the main intangible asset for companies used to create and use knowledge to increase firm value. The population in this study are non-financial companies listed on the Indonesia Stock Exchange in 2014-2021. The analysis method used in this study uses Moderated Regression Analysis. The study finds that the effect of intellectual capital has a significant effect on firm performance and risk, respectively. The moderating effect also affects the overall performance and market-side risk of the firm. Political connections make corporate decision-making inefficient. Future research can consider industry differences in the relationship of intellectual capital to firm performance and risk. This research has managerial implications, namely companies should consider increasing investment in the development and utilization of intellectual capital. Intellectual capital should be integrated into long-term corporate strategy. The limitations of this study are that the findings of this study are limited to developing countries and the need for more comprehensive measurements for intellectual capital.